Comprehensive evaluation of the nutritional value and contaminants of alfalfa (Medicago sativa L.) in China - Zhu, Xiaoyan; Chen, Wenxue; Li, Mengyao; Liu, Boshuai; Zhao, Shumin; Hu, Menglin; Li, Jiajing; Li, Defeng; Shi, Yinghua; Sun, Hao; Wang, Chengzhang (Frontiers in Nutrition, 2025)
IntroductionAlfalfa is used as a feed source for animals and plays an important role in animal nutrition. Nutritional value analysis and contamination evaluation are essential for sustainable utilisation to ensure the quality and safety of alfalfa.AimWe aimed to evaluate the nutritional value and safety of alfalfa in five major regions in China—the Northeast Plain (NP), Inner Mongolia Plateau (IMP), Northwest Desert Oasis (NO), Loess Plateau (LP), and Huanghuaihai Plain (HP).MethodsNinety-five samples representing 44 large-scale pratacultural companies were collected and analysed.ResultsThe average nutritional values of alfalfa hay were 16.43% crude protein (CP), 44.01% neutral detergent fibre (NDF), 33.22% acid detergent fibre (ADF), 10.78% crude ash (Ash), and 91.90% dry matter (DM), which were better in the NO and IMP areas; in particular, the α-linolenic acid value of alfalfa was the highest in the IMP area (p < 0.05). The detection rates of mycotoxins, microorganisms, and heavy metals were 100%. The over-standard rates of total bacteria count and total mould count were 66.7% and 75.8%, respectively, while the over-standard rate of chromium in heavy metals was as high as 87.9%.DiscussionThis study establishes the nutrient composition and harmful component profiles of alfalfa hay in five major planting areas for the first time, which provides a valuable reference for the safe and sustainable utilisation of alfalfa in livestock feed.